Use of Cistus aqueous extracts as botanical fungicides in the control of Citrus sour rot. (March 2017) - Karim, H.; Boubaker, H.; Askarne, L.; Cherifi, K.; Lakhtar, H.; Msanda, F.; Boudyach, E.H.; Ait Ben Aoumar, A.
Abstract: In this work, we investigated the in vitro and in vivo antifungal activity of aqueous extracts obtained from eight Cistus plant species against the development of Geotrichum citri-aurantii, the causal agent of citrus sour rot. The results demonstrate the in vitro effectiveness of all tested Cistus species aqueous extracts against G. citri-aurantii, the inhibition of mycelial growth ranged between 80 and 100%. Furthermore, Cistus aqueous extracts totally inhibited germination of G. citri-aurantii arthrospores at a concentration of 5 mg/mL. Among the plant species tested, C. laurifolius, C. salviifolius, C. monspeliensis, C. ladanifer and C. populifolius displayed the best fungistatic activity since the minimum inhibitory concentration (MIC) was <0.625 mg/mL. Under in vivo conditions, incidence of sour rot was lowered to 8.33% when fruits were treated with aqueous extracts of C. populifolius and C. creticus compared to 100% in the control. Disease severity was lowered to 3.74, 4.47 and 5.13% when fruits were treated with C. creticus, C. ladanifer and C. populifolius aqueous extracts, respectively. Using such these biopesticides in a replacement for synthetic fungicides or in combination with other established disease management practices could help control citrus postharvest decay in a more sustainable and eco-friendly way. Highlights: Aqueous extracts of all tested Cistus species revealed a highest significant antifungal activity. Cistus extracts fully inhibited the arthrospore germination at 5 mg/mL. Best sour rot control was obtained with C. populifolius and C. creticus extracts. Cistus aqueous extracts could be used as a potential source of antifungal compounds.